2015
DOI: 10.1103/physrevd.92.044040
|View full text |Cite
|
Sign up to set email alerts
|

Energy in first order2+1gravity

Abstract: We consider Λ=0 three dimensional gravity with asymptotically flat boundary conditions. This system was studied by Ashtekar and Varadarajan within the second order formalism -with metric variables-who showed that the Regge-Teitelboim formalism yields a consistent Hamiltonian description where, surprisingly, the energy is bounded from below and from above. The energy of the spacetime is, however, determined up to an arbitrary constant. The natural choice was to fix that freedom such that Minkowski spacetime has… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…3 Refer to an earlier work [71] for the second term in (3.8). 4 We can confirm the following equation…”
Section: Adding Boundary Termmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Refer to an earlier work [71] for the second term in (3.8). 4 We can confirm the following equation…”
Section: Adding Boundary Termmentioning
confidence: 99%
“…The remaining term of I GH (3.8) is Thus we can regard dn − [ω, n] = Dn a J a as the covariant derivative [71] where…”
Section: Gauge Invariancementioning
confidence: 99%
“…Both approaches were in the metric formulation. In contrast, Corichi et al in [8] adopted a first-order Hamiltonian formulation and showed that the results in both references [5] and [7] could be reproduced.…”
Section: Introductionmentioning
confidence: 96%
“…Further developments of the asymptotic flatness and the energy in 2 + 1 General Relativity can be found, for example, in Refs. [3,4,5].…”
Section: Introductionmentioning
confidence: 99%